Modified pulpotomy procedure in immature permanent teeth with apical periodontitis: a randomised controlled trial - Jun Wang; Wentao Shi; Wen Xiao; Zhengbing Chi (BMJ Open)
Objectives The objective of this study was to evaluate the effectiveness of a modified pulpotomy (MP) procedure in immature permanent teeth with apical periodontitis (AP).Design Randomised controlled trial.Setting One public hospital in Shanghai, ChinaParticipants A total of 33 teeth (31 patients) with a definitive diagnosis of AP with radiographic periapical radiolucency were recruited in this study. All the patients (teeth) completed the study accordingly.Methods and intervention Patients were randomly assigned to either MP or apexification treatment groups and were followed up for 12 months. Clinical symptoms and complications were recorded, and parallel periapical radiographic images were used to measure changes in root length and apical diameter. Wilcoxon’s rank sum test and Fisher’s exact test were used to compare the clinical and radiographic outcomes between MP and apexification, and analysed with analysis of variance.Main outcome measure The primary outcome was increase in root length at 12 months. The secondary outcomes included tooth survival, clinical success and decrease in apical diameter.Results MP group showed a significant increase in root length (10.05%±2.14% vs 1.16%±0.79%, p<0.05) at 12 months and a decrease in apical diameter (48.88%±10.42% vs 15.90%±8.88%, p<0.05) as compared with the apexification group. The tooth survival rate was 100%, and 90.91% (30/33) of teeth were asymptomatic with apical healing in both treatment groups (p>0.05).Conclusions MP can be an option for treating immature permanent teeth with AP. MP showed better performance in terms of continued root maturation than apexification. MP and apexification achieved comparable outcomes with regard to the resolution of clinical symptoms and apical healing.Trial registration number ChiCTR-INR-17012169.